Industrial Environmental Health as an Effort to Prevent Environmental Impacts and Occupational Diseases - Hardianti, Sri; Syifa Tanjung, Lailatul; Yusmita, Yesi; Irawan, Joni (Journal of Engineering Science and Technology Management, 2025)
Industrial activities have the potential to generate negative impacts on the environment and human health if they are not properly managed. Industrial environmental health plays a crucial role in preventing environmental pollution and occupational health disorders through the control of environmental factors and the implementation of industrial hygiene. This study aims to analyze the role of industrial environmental health in preventing the impacts of environmental pollution and occupational health problems. The research employed a literature review method using a qualitative descriptive approach, drawing on various sources such as scientific journals, textbooks, and regulations related to industrial environmental health. The findings indicate that controlling air emissions, managing liquid and solid waste, and implementing proper industrial hygiene can significantly reduce the risks of environmental pollution and occupational diseases. The optimal implementation of industrial environmental health is therefore an important strategy to support environmental sustainability and protect workers’ health.